(untitled) (Media Kesehatan Masyarakat Indonesia, 2018)
Efforts to achieve a healthy school free vectors need to be improved because of the increasing number of vector-transmitted diseases such as scabies, dermatitis, diarrhoea, typhoid, and dengue in students. Steps that can be taken to establish a clean and healthy lifestyle in preventing and controlling the disease vector breeding either by implementing the School-Based Vector Control (SBVC) in school. Application of this SBVC emphasis on awareness and concern of students in the control and the creation of a healthy environment. The research objective is the establishment of a model SBVC and gets an idea of the effectiveness of the model SBVC as improving the PHBs and the creation of a healthy environment to the students. The research was done in SMP Islam Sultan Agung 4, Semarang. The study population was all students of SMP Islam Sultan Agung 4 Semarang. Samples are students who have health problems and unhealthy as many as 30 students. This type of research is a Quasi-Experiments with non-randomized design one group pretest-posttest design. The data collection is done by observation, interviews, and questionnaires. The instrument of research is observation checklists and questionnaires. Univariate and bivariate data analysis by Wilcoxon statistical test. The results showed indicators of personal hygiene, hygiene in the classroom, cleanliness in toilets and ablution and cleanliness in the schoolyard before and after application of SBVC increased significantly (p <0.05). So that a clean and healthy living behaviour in students in the prevention and control of vector at school increased significantly (p = 0.00).